Atypical Histiocyte-Rich Sweet's Syndrome. (18th October 2017) - Chi, Sharon; Leung, Marcia; Carmichael, Mark; Royer, Michael; Cho, Sunghun
Abstract : Sweet's Syndrome is a rare neutrophilic dermatosis thought to be a result of immune dysregulation occurring in the setting of drug exposure, recent infection, pregnancy, and underlying malignancy or idiopathic with specific and widely accepted diagnostic criteria established in the literature. Other organ systems can be involved with varying degrees of severity. An unusual case of Sweet's Syndrome associated with myopericarditis, acral involvement, and atypical histological findings with predominance of histiocytes is described here.